Are generational differences just a myth? The role of generational stereotypes at work - Sousa, I.C.; Ramos, S.; Carvalho, H.; Standifer, R. (18th International Society for Justice Research (ISJR) Conference, 2021)
The topic of generations has been receiving a growing interest from scholars and practitioners. However, despite the extensive empirical research on generational diversity, findings are still mixed and unclear as some studies did not find support for generationally based differences (e.g., Costanza et al., 2012). In response, recent research has proposed perceived generational differences as a possible explanation for the inconsistencies found in the literature (e.g., Standifer & Lester, 2019). Perceived differences can be explained by the Social Identity Approach. Due to widespread stereotypes about generations, workers identify prototype characteristics of each generation and create impressions about what other generations value. With those stereotypes as references, workers tend to enhance perceived similarities within the ingroup and maximize the perceived differences between the ingroup and the outgroup, possibly believing that colleagues in their generation are more similar among them and more different from colleagues belonging to other generations. Therefore, we hypothesized that perceived generational differences in work values outnumber actual differences. A sample of 705 workers rated the degree to which they personally valued 15 work values, and then indicated value ratings for these items for each of the three generations: Baby Boomers, Generation X, and Generation Y. Categorical regression was used to test our hypothesis, including gender and education as control variables. Our hypothesis was supported. The high number of perceived generational differences suggests that individuals rely on stereotypes to identify and categorize a colleague as a member of a specific generation, which can lead to prejudice and, ultimately, trigger tensions.